A Clinical Investigation Into the Effects of Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Vaccination in Children With Acute Lymphoblastic Leukemia - Wu, Zhengcun; Jiang, Hongchao; Zhou, Yanan; Yang, Yun; Jiang, Haiyan; Zhang, Fang; Zhe, Linyang; Tang, Ruixia; Xu, Jianyu; Yan, Lingmei; Lu, Shuaiyao; Zhang, Tiesong; et al. (Journal of medical virology, 2025)
ABSTRACT This study systematically evaluated the humoral immune responses and cytokine profiles of 259 pediatric participants, comprising both healthy individuals and patients with Acute Lymphoblastic Leukemia (ALL), following either administration of an inactivated SARS‐CoV‐2 vaccine or natural infection. The data indicate that vaccination elicits measurable immune responses in both groups, supporting its relevance in immunocompromised pediatric populations. Although antigen‐specific responses to the spike (S) protein and receptor‐binding domain (RBD) were attenuated in the ALL cohort, levels of neutralizing antibodies and antibodies capable of inhibiting RBD‐ACE2 binding were comparable to those in healthy controls, suggesting that functional antibody‐mediated immunity can still be achieved in ALL patients. Notably, vaccinated ALL patients exhibited higher neutralizing antibody titers against the SARS‐CoV‐2 prototype strain and major variants of concern (Alpha, Beta, Delta) than their healthy counterparts. However, both groups demonstrated markedly reduced responses to the Omicron variant, underscoring its substantial immune escape potential. Cytokine analysis revealed dysregulated expression patterns in the ALL group, with minimal modulation following vaccination, in contrast to the immunosuppressive cytokine regulation observed in healthy individuals. Importantly, the JAK/STAT signaling pathway emerged as a key component in the immune response to SARS‐CoV‐2 among healthy subjects. These insights provide a scientific basis for the optimization of COVID‐19 immunization strategies tailored to vulnerable pediatric groups.